CULTURAL LINGUISTICS PERSPECTIVE: UNDERSTANDING LANGUAGE THROUGH CULTURE (American Journal of Interdisciplinary Research and Development, 2024)
Language and culture are discussed in this article. Some examples are given in English and Uzbek as well as. The importance of culture in linguistics mentioned. Difficulties which translator face up during the conversations are given.